COVID-19, health care and self-medication issues in resource-limited settings: Findings and implications based on experiences in Ghana - Israel Abebrese Sefah; Darius Obeng Essah; Mainul Haque; Sylvia A Opanga; Santosh Kumar; Ibrahim Chikowe; Dan Kibuule; Enos M Rampamba; Aubrey C Kalungia; Thuy Nguyen Thi Phuong; Zikria Saleem; Vanda Markovic-Pekovic; et al. (Advances in Human Biology, 2021)
Introduction and Objectives: There have been concerns with the level of misinformation regarding coronavirus disease 2019 (COVID-19) and its treatment, drug shortages, as well as increased use and prices of anti-malarials, antibiotics and hygiene products during the recent pandemic. Community pharmacists can play a significant role in disease prevention and treatment in the fight against COVID-19 including providing hygiene information and medicine availability across Africa and generally. Consequently, there is a need to review the role of community pharmacists in preventing unintended consequences during any pandemic as well as the impact of COVID-19 on the demand, availability and prices of suggested medicines for its management. Materials and Methods: Multiple approaches involving a qualitative review of the management of COVID-19 across countries coupled with a pilot study in Ghana among six purposely selected community pharmacists during the early stages of the pandemic assessing patterns of demand, availability and prices of medicines suggested for the management of COVID-19. Alongside this, pharmacists' future role enhancing appropriate medicine use in Ghana and wider combined with the help of senior level co-authors. Results: The majority (five out of six) of pharmacists in Ghana reported increased demand for hydroxychloroquine, antibiotics and vitamins as immune boosters resulting in shortages with price increases particularly for anti-malarials. Conclusion: The global lockdown had impacted on the supply and prices of medicines in Ghana similar to other countries. Community pharmacists can play a key role with encouraging safe medicine use, reducing self-purchasing of medicines and planning workflows during future pandemics including vaccinations. They can also help address potential misinformation and its consequences as well as the unintended consequences of pandemics including better management of non-communicable diseases.